Vehicle avoidance: The hierarchy of visual attention towards animals, plants, and vehicles - Chihiro Kioka; Kunihito Tobita (PLoS ONE, 2025)
The biophilia hypothesis posits that humans have an innate affinity for nature, with natural landscapes effortlessly capturing their attention, and a tendency to seek nature. The animate monitoring hypothesis suggests that humans have evolved to quickly detect and respond to animals for survival. The plant awareness disparity hypothesis argues that people notice plants less than animals due to perceptual biases and preferences. Based on these hypotheses, it was predicted that people’s visual attention would be superior towards animals, plants, and manufactured objects, in that order. This study investigated the hierarchy of visual attention towards animals (birds, mammals and humans), plants (fruit), and manufactured objects (vehicles) using a dot-probe task framework. The findings revealed no significant differences in reaction time or attentional bias for animal or plant stimuli. In contrast, perceptual processing was inhibited when viewing a vehicle and attentional avoidance occurred, resulting in slower reactions than to animals or plants. These findings offer partial support for the proposed hierarchy of visual attention, suggesting that while natural stimuli such as animals and plants receive comparable attention, some manufactured objects may elicit perceptual avoidance.